Website Content Evaluation Instrument for Adoption of Digital Publishing Innovations (International Journal of Scientific Research and Management (IJSRM), 2016)
Digital publishing is currently a major area of growth in the publishing sector of the global economy and publishers, in realization of this development, are increasingly going digital, and going digital entails adopting at least some of the innovations necessary for profitable business. To understand which innovations that are adopted by pioneer e-publishers to assess them for possible adoption, scholars and publishers, especially those based in developing economies would need reliable website evaluation instruments, but most instruments available for website analysis are not focused on publishing. This gap, therefore, needs to be filled with instruments specifically targeted at publishing sites. This study reports the development procedure for a web evaluation instrument targeting publishing-specific websites. The 34-item instrument measures five aspects of digital publishing: digital book format, e-promotion, e-commerce, e-collaboration and esocialization. A total of 79 websites were observed and the proposed instrument was used to collect data to examine level or extent of implementation of digital publishing. The results indicate that the instrument is reliable. It is, therefore, concluded that the instrument will be useful to media scholars and publishers.